INOVASI HAK CIPTA DALAM BISNIS DAN INDUSTRI MUSIK DALAM KOMUNIKASI MASSA - Ahmad Budi Sulistio Yuwono, S.E., M.M, Ahmad Budi Sulistio Yuwono, S.E., M.M (Akademi Komunikasi SAE Indonesia, 2023)
In our increasingly modern world, the digital era brings various kinds of changes in people's behavior in all areas of life. This is no exception in the field of copyright protection, which is part of intellectual property. The task of artist management is to organize or regulate the professional life of celebrities such as actors, artists, singers, models, and other figures in the entertainment industry. Without artist management, artists have difficulty organizing their lives, from managing schedules to negotiating commissions. How does artist management help ensure legal protection, specifically intellectual property protection for responsible artists? And how does Artist Management use evolving technology to innovate and protect the intellectual property rights of the artists they manage and sponsor? The objectives of this study are: 1). To know and research how Innovation in Artist Management can help IPR Protection in today's digital era. 2). To know and research what challenges are faced in Creating and implementing innovations by Artist Management to help IPR Protection in today's digital era. The research method is comparative legal research. In conclusion Flexibility and Adaptability: The entertainment industry is constantly evolving and changing rapidly. Artist managers need to have a flexible attitude and be able to adapt to such changes. Be prepared to adjust your strategy, seek new opportunities, and deal with challenges as they arise. The ability to adapt quickly will allow artist managers to stay relevant and help artists deal with changes in the industry.